2018
DOI: 10.1371/journal.pone.0199058
|View full text |Cite
|
Sign up to set email alerts
|

Anal HPV infection and correlates in HIV-infected patients attending a Sexually Transmitted Infection clinic in Brazil

Abstract: ObjectiveTo estimate the prevalence of anal HPV infection, genotype distribution, intraepithelial neoplasia (AIN) and correlates in a cohort of HIV-infected patients attending at Sexually Transmitted Infections (STI) clinic in Brazil.Study designA descriptive analysis was performed which includes, demographic, behavioral and clinical data. Anal specimens from HIV-positive men and women were collected during a regular visit and they were used for cytology and histopathology tests, as well as for HPV molecular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…The sole protective factor against infection was ART that included integrase inhibitors (OR: 0.508, 95% CI: 0.277-0.935). These data confirm recent observations of the protective effects of ART and CD4 levels>500 cells/uL against infection by oncogenic HPV genotypes [26]. Other studies have described the presence of genital warts [27] and a deficient immune system [28] as risk factors for developing neoplasias associated with HR-HPV infection.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The sole protective factor against infection was ART that included integrase inhibitors (OR: 0.508, 95% CI: 0.277-0.935). These data confirm recent observations of the protective effects of ART and CD4 levels>500 cells/uL against infection by oncogenic HPV genotypes [26]. Other studies have described the presence of genital warts [27] and a deficient immune system [28] as risk factors for developing neoplasias associated with HR-HPV infection.…”
Section: Discussionsupporting
confidence: 90%
“…Both samples were immersed in thinlayer liquid medium and sent to the pathology laboratory of the hospital. Genotypes 16,18,26,31,33,35,39,45,[51][52][53]56,58,59,66,68,73, and 82 were considered to be HR-HPV genotypes. Genotypes 6,11,34,40,[42][43][44]54,55,57,61,[70][71][72]81,83,84, and 89 were considered to be low-risk (LR-HPV) genotypes.…”
Section: Designmentioning
confidence: 99%
“…Compared to the literature, these numbers are low . We assume that this observation is related to the good access to medical care, resulting in early diagnosis of HIV and HPV infection, easy access to antiretroviral therapy and better adherence to therapy . Our cohort also includes both genders regardless of sexual orientation while previous studies often concentrated on MSM only.…”
Section: Discussionmentioning
confidence: 94%
“…Another study, conducted in Spain, found a rising trend in the cases of gonorrhea, which was more pronounced among MSM [17]. A recent analysis showed that being MSM represented a risk factor for both HPV and multiple infections [18]genotype distribution, intraepithelial neoplasia (AIN). Our survey confirmed that co-infection is quite common (one in three of our MSM with STIs), and found gonorrhea the most often reported infection (18%).…”
Section: Discussionmentioning
confidence: 99%
“…Having multiple sexual partners is common in the MSM community, and still many do not use condoms consistently. Recent data indicated that less than 60% of MSM reported using a condom [18]genotype distribution, intraepithelial neoplasia (AIN, and evidence of a limited use of condoms emerged from another study too [19]. One of the reasons for this situation lies in that “safer sex” campaigns have lost traction in this population.…”
Section: Discussionmentioning
confidence: 99%